Implementasi Pembuatan APE dalam Kegiatan Bermain Melalui Pelatihan Clay Art dan Seni Di Desa Dayah Mesjid - Sari Rizki; Rahma; Riswandi; Fauziatul Halim (LPPM Umuslim, 2022)
The goal to be achieved in the service activities of lecturers and students of PG PAUD Universitas Almuslim, is the creation of fun learning for children by applying educational game tools (APE) so that children's creativity emerges by involving children in the manufacturing process, and in playing and study. In making educational teaching aids, it is not as easy as imagined because teachers have to consider aspects ranging from planning the selection of learning media which include (1) planning learning in PAUD and (2) learning targets, namely children (3) the level of media readability does it meet the technical requirements such as clarity, size, color arrangement (4) Conformity to the situation and condition of the place, such as land area, institutional environment, and community resources around the institution and the fifth Objectivity must avoid choosing media based on personal pleasure alone. In this activity, the teacher has given an understanding of the importance of making educational aids in every learning in PAUD because teaching aids can foster children's imagination and will be by children's growth and development.